Vertebral Fractures and Spondylosis in Men - Original Investigation - Selmin Gülbahar; Canan Altay; Gözde Özcan Söylev; Özlem El; Çiğdem Bircan; Metin Manisalı; Özlen Peker; Meltem Baydar; Sema Öncel (Galenos Yayinevi, 2008)
Aim: The aim of this study was to investigate the relationship between vertebral fractures and spondylosis and bone mineral density in men older than 60 years. Material and Method: Thirty-two men with back and low back pain aged over 60 years were included into the study. Thoracic and lumbar spine radiographs were taken and, anterior, central and posterior heights of each vertebral body from T4 to L5 was measured and than the number of vertebral fractures was assessed. Osteophyte and disc scores were used for evaluation of spondylosis. Bone mineral density was measured by dual-energy-X-ray absorptiometry. Measurements were obtained from lumbar vertebrae and proximal femoral region. Results: Significant positive correlations were found between vertebral fracture and osteophyte score and bone mineral density of total femoral region. When osteophyte score and total femoral bone mineral density were taken into consideration, there were no significant correlations between other parameters and vertebral fracture. Significant positive correlations were observed between osteophyte score and bone mineral density and t scores of L1-4. Also there were significant positive correlations between disc score and both bone mineral density and t scores of L1-4. Significant positive correlation was also found between femoral bone density and body weight. Conclusion: Finally, lumbar bone mineral density increases with spinal degenerative changes, but the increase in bone mineral density can not prevent sub clinic vertebral fractures. Especially, in the men who have intensive spinal degenerative changes, the measurement of lumbar bone mineral density is not enough for determining the fracture risk. Measurement of femoral bone mineral density and evaluation of clinic risk factors are more important for determining the fracture risk. (From the World of Osteoporosis 2008;14:1-6)